Determinan Environmental, Social, And Governance (ESG) (Studi Empiris Perusahaan Di Indonesia Yang Terdaftar Di IDX 2018-2021) - Vivianita, Alfa; Roestanto, Anantya; Indudewi, Dian (Jurnal Dinamika Ekonomi dan Bisnis, 2024)
Institutional theory suggests that company policies are likely to be altered when they experience three types of influences: coercive, normative, and mimetic isomorphism. These three occurrences prompted companies to engage in activities related to Environmental, Social, and Governance (ESG). The majority of previous researches had primarily examined the relationship between ESG factors and financial performance, firm value, and information asymmetry. One way to address the existing research gaps is by undertaking research on ESG factors, considering the impact of variables such as the size and age of the company, the industry it operates in, and its institutional ownership. The objective of this research is to conduct an ESG analysis, considering factors such as company size, company age, industry type, and institutional ownership. This research employed a quantitative methodology as its approach. This research utilized secondary data. The sampling method employed was purposive sampling. The utilization of multiple linear regression analysis was employed for the analysis. The findings of the study showed that the nature of the industry influenced the ESG performance, while the size of the company, its age, and ownership structure did not have any impact on ESG